City Resilience to Population Ageing In the Context of Spatial (In)Accessibility. The Case of Poznań and Łódź - Lechowska, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The ageing of the society is a serious factor affecting the prospects of urban development. Unfavourable demographic changes disturb the functioning of the urban system, thus forcing adaptive activities leading to a new state of balance in the organism of a city. The ageing of urban society requires a new look at the organisation of space in the city. The importance of planning age‑friendly cities is rising fast. Due to the low mobility of the elderly, it is important to plan their direct living environment, ensuring access to facilities or areas that meet the basic needs of this particular group of urban space users. As part of the answer to the question: to what extent the cities of Poznań and Łódź are resilient to the ageing process in spatial terms, an analysis was performed of the accessibility of green areas, sports and recreation facilities, service and commercial, cultural, healthcare facilities and public transport stops for the elderly population. This resulted in the delimitation of problem areas characterised by functional and spatial deficits and the development of the two cities’ resilience indexes to demographic changes, namely, ageing in spatial terms.